The prevalence of selected potentially hazardous workplace exposures in the US: Findings from the 2010 National Health Interview Survey12. Issue 6 (20th July 2012) - Calvert, Geoffrey M.; Luckhaupt, Sara E.; Sussell, Aaron; Dahlhamer, James M.; Ward, Brian W.
Abstract Objective Assess the national prevalence of current workplace exposure to potential skin hazards, secondhand smoke (SHS), and outdoor work among various industry and occupation groups. Also, assess the national prevalence of chronic workplace exposure to vapors, gas, dust, and fumes (VGDF) among these groups. Methods Data were obtained from the 2010 National Health Interview Survey (NHIS). NHIS is a multistage probability sample survey of the civilian non‐institutionalized population of the US. Prevalence rates and their variances were calculated using SUDAAN to account for the complex NHIS sample design. Results The data for 2010 were available for 17, 524 adults who worked in the 12 months that preceded interview. The highest prevalence rates of hazardous workplace exposures were typically in agriculture, mining, and construction. The prevalence rate of frequent handling of or skin contact with chemicals, and of non‐smokers frequently exposed to SHS at work was highest in mining and construction. Outdoor work was most common in agriculture (85%), construction (73%), and mining (65%). Finally, frequent occupational exposure to VGDF was most common among mining (67%), agriculture (53%), and construction workers (51%). Conclusion We identified industries and occupations with the highest prevalence of potentially hazardous workplace exposures, and provided targets for investigation and intervention activities. Am. J. Ind. Med. 56:635–646, 2013. © 2012 Wiley Periodicals, Inc.